The Development of the Written Culture in Eastern Bulgaria Before 971 - Юрьевич Темчин, Сергей (Slavistica Vilnensis, 2000)
The history of the Eastern Bulgarian written culture of 680–971 can be divided into five periods: 1) 680–864, e.g., the period of the pre-Christian Bulgarian state, with a rudimentary written tradition in place; 2) 864–886, the point of culmination of Greek literacy in Christian Bulgaria before the arrival of Slavic bookmen expelled from Pannonia; 3) 886–893, the preparatory stage for the introduction of Church Slavonic liturgical books into official use; 4) 893–927, the reign of Tsar Symeon, when the Cyrillic alphabet was created and used as a specifically secular writing system; 5) 927–971, the reign of Tsar Peter and Tsar Boris II, when Church Slavonic liturgical books in Eastern Bulgaria were transcribed from Glagolitic into Cyrillic (presumably in the 930’s–940’s).